The artful universe expanded - Barrow, John D., 1952-2020 (Oxford University Press, 2005)
"In this wide-ranging exploration, John D. Barrow shows how our size, our form, and our aesthetic sensibilities are all moulded by the physical nature of the universe we inhabit. He explores the underlying mathematical relationships and patterns behind some of our art and music and their connections with natural forms, and draws out the ways in which the rhythms of our world - of day and night, and the yearly cycle of seasons - have impinged on the human psyche throughout history." "Originally published in 1995, this new edition has been updated and enlarged. From fundamental forces, multiverses, and evolution of complexity, to the patterns in the night sky, the beauty of vases, the music of Bach, Masaccio's use of perspective, and the fractal nature of Jackson Pollock's art, this book unveils a varied series of surprises that reveal how our existence and culture are framed and guided by the fundamental physical and mathematical structure of our artful universe."--Jacket